THE EFFECT OF PRICE AND EWOM TOWARD CUSTOMER VALUE AND THE IMPLICATION TO CUSTUMER LOYALTY IN KINGS’ COFFEE STORE - Rahmat Hidayat; Sutrisna Sutrisna; Nandan Limakrisna (Strategic Management Business Journal, 2023)
This study aims to determine the effect of price and ewom toward customer value and the implication to custumer loyalty at Kings’ coffee shops, considering the large number of visitors who come even though there are many coffee shops in Cikarang, therefore researchers want to conduct research on these coffee shops, with the object of research at the Kings’ shop and the population used is all coffee shop visitors and the sample is 191 respondents. Based on the results of the research and discussion of the results of research data analysis described in the previous chapter, the conclusion of this study is that price has possitive effect to value custumer but has no positive and significant effect on custumer loyalty at the Kings’ Coffee Shop, Ewom has a positive and significant effect on the custumer value and custumer loyalty of the Kings’ Coffee Shop. Simultaneously, Ewom and price have a simultaneous effect on custumer value at Kings’ coffee shops and price, ewom and custumer value has possitve effect toward custumer loyalty. In this research, custumer value is full mediating variable. JEL Classification: M31, O14